Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/smll.202000892
|View full text |Cite
|
Sign up to set email alerts
|

Three Decades of Research about the Corona Around Nanoparticles: Lessons Learned and Where to Go Now

Abstract: This will be a more challenging task than just detect them in the corona.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 51 publications
(90 reference statements)
0
41
0
Order By: Relevance
“…Recent advancements in intra-articular drug delivery have leveraged both small sizes and electrostatic interactions with the anionic ECM 2,3. . It is well known that micro-and nanoscale drug delivery approaches are immediately subjected to the high abundance of host-derived biological components such as proteins, carbohydrates, and lipids 4 . These bioactive components can alter the size and surface composition of the particles and equip them with a distinct biological identity, in turn, dictating their physiological and therapeutic outcomes 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advancements in intra-articular drug delivery have leveraged both small sizes and electrostatic interactions with the anionic ECM 2,3. . It is well known that micro-and nanoscale drug delivery approaches are immediately subjected to the high abundance of host-derived biological components such as proteins, carbohydrates, and lipids 4 . These bioactive components can alter the size and surface composition of the particles and equip them with a distinct biological identity, in turn, dictating their physiological and therapeutic outcomes 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that micro-and nanoscale drug delivery approaches are immediately subjected to the high abundance of host-derived biological components such as proteins, carbohydrates, and lipids 4 . These bioactive components can alter the size and surface composition of the particles and equip them with a distinct biological identity, in turn, dictating their physiological and therapeutic outcomes 4,5 . For instance, studies on systemic administration have shown that just a simple change from blood plasma to serum had a profound difference in both protein corona composition and nanoparticle (NP) fate, demonstrating the importance of selecting the appropriate environment to account for in vivo settings 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Another crucial aspect is experimental obstacles affecting the characterization of NPs and their corona profiles. Using diluted NPs to study biomolecular/protein corona is one practical approach that can minimize such impurity issues 110 , 111 .…”
Section: Introductionmentioning
confidence: 99%
“…Yet so far, no studies have addressed the potential effect of the synovial fluid composition on such drug delivery vehicles, which is vital to understand and predict pharmacokinetic profiles and behaviors. For systemic administration, it is well known that micro and nanoscale drug delivery approaches are immediately subjected to the high abundance of host-derived biological components such as proteins, carbohydrates, and lipids 5 . These bioactive components can alter the size and surface composition of the particles and equip them with a distinct biological identity, in turn, dictating their physiological and therapeutic outcomes .…”
Section: Introductionmentioning
confidence: 99%